2017
DOI: 10.30605/ethicallingua.v4i2.629
|View full text |Cite
|
Sign up to set email alerts
|

Using Noddy Cartoon to Improve the Writing Skill of the First Year Students of SMK Terpadu Mega Rezky Makassar

Abstract: This research is conducted to find out: (1) whether or not the use of Noddy cartoon is effective in improving the writing skill of the first year students of SMK Terpadu Mega Rezky Makassar and (2) the attitude of the first year students of SMK Terpadu Mega Rezky Makassar toward the use of Noddy cartoon in improving their writing skill. The research employs quasi-experimental method with two groups namely control and experimental groups. Each group consists of 30 students. The sample is chosen by applying clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Further, another research brought by Tanasy (2017) discussed English television show entitled Make Way for Noddy concluded that the use of Noddy cartoon can improve the learners' English ability and change their attitude as well into positive in learning English after being treated with several Noddy cartoon episodes. This experimental study also found that the learners' learning ability indicated a significant difference through their academic scores after being treated by this show to compare with those who just treated with conventional way.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, another research brought by Tanasy (2017) discussed English television show entitled Make Way for Noddy concluded that the use of Noddy cartoon can improve the learners' English ability and change their attitude as well into positive in learning English after being treated with several Noddy cartoon episodes. This experimental study also found that the learners' learning ability indicated a significant difference through their academic scores after being treated by this show to compare with those who just treated with conventional way.…”
Section: Review Of Literaturementioning
confidence: 99%